Inhibitors of NLRP3 Inflammasome Formation: A Cardioprotective Role for the Gasotransmitters Carbon Monoxide, Nitric Oxide, and Hydrogen Sulphide in Acute Myocardial Infarction - Payne, Fergus M.; Dabb, Alisha R.; Harrison, Joanne C.; Sammut, Ivan A. (International journal of molecular sciences, 2024)
Myocardial ischaemia reperfusion injury (IRI) occurring from acute coronary artery disease or cardiac surgical interventions such as bypass surgery can result in myocardial dysfunction, presenting as, myocardial “stunning”, arrhythmias, infarction, and adverse cardiac remodelling, and may lead to both a systemic and a localised inflammatory response. This localised cardiac inflammatory response is regulated through the nucleotide-binding oligomerisation domain (NACHT), leucine-rich repeat (LRR)-containing protein family pyrin domain (PYD)-3 (NLRP3) inflammasome, a multimeric structure whose components are present within both cardiomyocytes and in cardiac fibroblasts. The NLRP3 inflammasome is activated via numerous danger signals produced by IRI and is central to the resultant innate immune response. Inhibition of this inherent inflammatory response has been shown to protect the myocardium and stop the occurrence of the systemic inflammatory response syndrome following the re-establishment of cardiac circulation. Therapies to prevent NLRP3 inflammasome formation in the clinic are currently lacking, and therefore, new pharmacotherapies are required. This review will highlight the role of the NLRP3 inflammasome within the myocardium during IRI and will examine the therapeutic value of inflammasome inhibition with particular attention to carbon monoxide, nitric oxide, and hydrogen sulphide as potential pharmacological inhibitors of NLRP3 inflammasome activation.